EVALUATION OF WORKSHOP ROOM COMFORT TO IMPROVE OCCUPATIONAL HEALTH AND SAFETY (OHS) - Pratama Putra, Andi Andre; Suharto, Moh Fachruddin; Attaufiq, Muhammad Muhdi; Watung, Maranatha E. (Border: Jurnal Arsitektur, 2025)
The establishment of a comfortable and safe work environment is fundamental to facilitate worker productivity and well-being. The workshop room, as one of the prime facilities in the workings of discovery and practice, must have light conditions, thermal comfort, and noise levels in accordance with occupational health and safety standards. The purpose of the study is to assess the light conditions, thermal comfort, and noise levels in the workshop room and provide strategic recommendations to improve the quality of the working environment. The research methodology employed is quantitative, where direct measurements are made with respect to the lighting levels, temperature, humidity, airspeed, and noise levels in the workshop room. The data were obtained to compare it with the relevant standards to determine whether the work environment conditions comply with the required regulations. The outcomes of the study reveal that lighting conditions in the workshop room do not meet the recommended levels entirely, especially in some work areas where light intensity is below the suggested threshold. The other major concern is thermal comfort because the room users would not be comfortable under very high temperature and humidity conditions. Noise levels, however, were found to be below standard. However, these noise levels which are almost hitting the upper limit could affect work comfort and health. Hence, with respect to these findings, the study recommends the redesigning of the lighting layout, improving the ventilation system, and applying noise abatement methods to raise the quality of the workshop room working environment.